Prolyl oligopeptidase inhibition reduces oxidative stress via reducing NADPH oxidase activity by activating protein phosphatase 2A - Eteläinen T; Kulmala V; Svarcbahs R; Jäntti M; Myöhänen TT (ELSEVIER SCIENCE INC, 2022)
Oxidative stress (OS) is a common toxic feature in various neurodegenerative diseases. Therefore, reducing OS could provide a potential approach to achieve neuroprotection. Prolyl oligopeptidase (PREP) is a serine protease that is linked to neurodegeneration, as endogenous PREP inhibits autophagy and induces the accumulation of detrimental protein aggregates. As such, inhibition of PREP by a small-molecular inhibitor has provided neuroprotection in preclinical models of neurodegenerative diseases. In addition, PREP inhibition has been shown to reduce production of reactive oxygen species (ROS) and the absence of PREP blocks stress-induced ROS production. However, the mechanism behind PREP-related ROS regulation is not known. As we recently discovered PREP's physiological role as a protein phosphatase 2A (PP2A) regulator, we wanted to characterize PREP inhibition as an approach to reduce OS. We studied the impact of a PREP inhibitor, KYP-2047, on hydrogen peroxide and ferrous chloride induced ROS production and on cellular antioxidant response in HEK-293 and SHSY5Y cells. In addition, we used HEK-293 and SH-SY5Y PREP knock-out cells to validate the role of PREP on stress-induced ROS production. We were able to show that absence of PREP almost entirely blocks the stressinduced ROS production in both cell lines. Reduced ROS production and smaller antioxidant response was also seen in both cell lines after PREP inhibition by 10 mu M KYP-2047. Our results also revealed that the OS reducing mechanism of PREP inhibition is related to reduced activation of ROS producing NADPH oxidase through enhanced PP2A activation. In conclusion, our results suggest that PREP inhibition could also provide neuroprotection by reducing OS, thus broadening the scope of its beneficial effects on neurodegeneration.